Pelatihan Penerapan Teknologi Alat Produksi dan Pengemasan bagi UMKM Labuana Kota Banjarbaru Kalimantan Selatan - Normaidah, Normaidah; Mazdadi, Muhammad Itqan; Ratnapuri, Prima Happy; Buih, Putri Helena Junjung (Jurnal Pengabdian UNDIKMA, 2025)
This community service aims to improve the skills of UMKM Labuana in applying production equipment technology and product packaging instruments. The methods used include initial surveys, followed by technology application training, and evaluation with observation methods on improving partner skills in the equipment used. The results of this service show that the increasing skills of UMKM Labuana in applying product production and packaging technology include installation, operation, and maintenance of equipment.